If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + -6 = 12 Reorder the terms: -6 + 9y = 12 Solving -6 + 9y = 12 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 9y = 12 + 6 Combine like terms: -6 + 6 = 0 0 + 9y = 12 + 6 9y = 12 + 6 Combine like terms: 12 + 6 = 18 9y = 18 Divide each side by '9'. y = 2 Simplifying y = 2
| x(6x-9)=0 | | 6x-7+4x+7+20x+5=180 | | m-(-13)=36 | | -(8/9)x-(-(8/9)-2) | | -160+9x=60-2x | | 4e(6x+4)=8 | | 2x+30+x+40+2x+75+3x-5=90 | | 2x+30+x+40+2x+75+3x-5=180 | | 2x+30+x+40+2x+75+3x-5=360 | | -7x-32=-11x+56 | | 3/y=12 | | 3+9x=4(x+7) | | -63-4x=21-7x | | 0=5y^2-11y+10 | | x+4.2=1.6 | | 15+3e^2x-7=91 | | -68-2x=-12x+152 | | 2x=8/4 | | x^2+ax+18=0 | | 4(z-1)=26 | | 3y+4y-5=23 | | 155=-16(3+3d) | | 4x-24=18+x | | d=1/3(3.14)(r^2)(m) | | x^3+3x=67 | | 9f+3.6=108 | | -142=4x+18 | | 7a+8b+2a+3b= | | 3x^2+2x-7-8=0 | | 13=34+6x | | 2x+3x+6x+5y= | | 2(3w-4)=4(w+3) |